Salmonella DNA Adenine Methylase Mutants Confer Cross-Protective Immunity - Heithoff, Douglas M. (American Society for Microbiology, 2001)
Salmonella isolates that lack or overproduce DNA adenine methylase (Dam) elicited a cross-protective immune response to different Salmonella serovars. The protection afforded by the Salmonella enterica serovar Typhimurium Dam vaccine was greater than that elicited in mice that survived a virulent infection. S. enterica serovar Typhimurium Dam mutant strains exhibited enhanced sensitivity to mediators of innate immunity such as antimicrobial peptides, bile salts, and hydrogen peroxide. Also, S. enterica serovar Typhimurium Dam(−) vaccines were not immunosuppressive; unlike wild-type vaccines, they failed to induce increased nitric oxide levels and permitted a subsequent robust humoral response to diptheria toxoid antigen in infected mice. Dam mutant strains exhibited a low-grade persistence which, coupled with the nonimmunosuppression and the ectopic protein expression caused by altered levels of Dam, may provide an expanded source of potential antigens in vaccinated hosts.